The Effect of ICSR Disclosure and ICG Disclosure on the Profitability of Sharia Commercial Banks - Daniel Kesuma; Wan Fachruddin (International Journal of Society and Law, 2024)
This study was directed fully intent on deciding the impact of ICSR disclosure and ICG disclosure on Profitability (ROE) in Sharia Commercial Banks enlisted with the OJK for the 2019-2023 period. The population in this study is 14 Sharia Commercial Banks enlisted with the OJK for the 2019-2023 period. By using purposive sampling, a sample of 8 Sharia Commercial Banks with 5 years of annual report observation was. Data analysis includes qualitative descriptive analysis, classical assumption test (normality test, multicollinearity test, heteroscedasticity test and autocorrelation test with Durbin-Watson), multiple linear regression analysis, correlation coefficient and determination analysis, and hypothesis test (t-test and F-test) by using SPSS version 26 software. The results of the study show that ICSR partially has no effect and is not significant on profitability, while ICG partially has a significant effect on profitability. Simultaneously, the research results show that ICSR and ICG have a significant effect on the profitability of Sharia Commercial Banks enlisted with the OJK for the 2019-2023 period.